1530. De-implementation Strategy to Reduce the Inappropriate Use of Urinary and Intravenous CATheters: the RICAT Study. (26th November 2018) - Laan, Bart J; Spijkerman, Ingrid J B; Godfried, Mieke H; Pasmooij, Berend C; Borgert, Marjon J; Maaskant, Jolanda M; Opmeer, Brent C; Vos, Margreet C; Geerlings, Suzanne E
Abstract: Background: Catheter-associated urinary tract infection (UTI) and catheter-associated bloodstream infection (BSI) are common healthcare-associated infections (HAI). Therefore, catheters should only be used if indicated. However, based on the literature up to 65% of the urinary catheters and 56% of the peripheral intravenous catheters have an inappropriate indication. So, an efficient way to reduce HAIs is to avoid unnecessary use of catheters. Our quality improvement project aims to reduce unnecessary use of catheters. Methods: In a multicenter, interrupted time series study, several interventions to avoid inappropriate use of catheters were carried out in internal medicine and nonsurgical subspecialty wards in seven hospitals in the Netherlands. The indications for catheter use were based on (inter)national guidelines. The primary endpoint is the percentage of inappropriate indications on the day of data collection. Secondary endpoints are catheter-associated infections, length of hospital stay and mortality. Data were collected once per 2 weeks during baseline (7 months) and post-intervention (7 months). Preliminary analyses compared incidence rates before and after the intervention. Results: Data were obtained from 5, 691 observed patients. The rate of inappropriate use of urinary catheters decreased from 32.1 to 23.7% (incidence rate ratio 0.74, 95% CI 0.58–0.94, P = 0.013), and inappropriate use of peripheral intravenous catheters decreased from 22.0 to 15.2% (incidence rate ratio 0.69, 95% CI 0.60–0.80, P < 0.001). The overall urinary and intravenous catheter use was stable, resp. 12.2% ( n = 324) to 12.5% ( n = 380) and 62.8% ( n = 1, 665) to 62.1% ( n = 1, 887). Most inappropriate indications were due to prolonged catheter use. The indications which expire frequently are"Accurate measurements of urinary output in critically ill patients' for urinary and"IV fluids and antibiotic therapy' for intravenous catheters. Subsequent analyses will take into account the interrupted time series design, and evaluate catheter-associated UTI and BSI rates. Conclusion: Our de-implementation strategy reduces unnecessary use of urinary and intravenous catheters in non-ICUs. It is important to increase awareness for inappropriate use of catheters. Disclosures: S. E. Geerlings, Nordic Pharma: Consultant and Fosfomycin iv, consulting fee.